Flight energetics, caste dimorphism and scaling properties in the bumblebee Bombus impatiens - Billardon, Fannie; Darveau, Charles-A. (Université d'Ottawa | University of Ottawa, 2019)
Animal size affects energetics of locomotion. Using female caste dimorphism in bumblebees, we assessed how body mass impacted morphological and physiological traits linked with flight. The allometric relationships obtained for workers wing surface area, wingbeat frequency, flight and resting metabolic rates could predict the trait values of queens that are more than four-fold larger. Flight success of queens decreased over time in part due to a large increase in body mass, and decrease in traits linked with flight, namely wingbeat frequency, metabolic rate, and the activity of metabolic enzymes tended to decrease. After taking into account temporal changes, body mass, flight wingbeat frequency and metabolic rate were repeatable. Finally, we found significant family resemblance for all traits measured, indicating that shared genes and/or environmental effects impact phenotypic variation. Together, we here show that the functional association between body morphology and flight physiology is robust, providing further insights into the mechanistic basis of metabolic rate scaling patterns during locomotion in animals.
Keywords: Metabolic rate, Flight, Wingbeat frequency, Muscle, Enzyme, Allometry